2004
DOI: 10.1128/jcm.42.11.5424-5426.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Confirmation of Quinine-Resistant Plasmodium falciparum Malaria Followed by Postmalaria Neurological Syndrome in a Traveler from Mozambique

Abstract: A case of quinine-resistant Plasmodium falciparum malaria, followed by a postmalaria neurological syndrome and a recurrence episode, is described. Genetic characterization of the P. falciparum isolate obtained by analysis of msp1 and msp2 amplicons revealed the coexistence of two genotypes causing the first malaria episode and the presence of a unique isolate responsible for the recurrence. CASE REPORTFifteen days after returning from Bilene (Maputo Province, Mozambique), a previously healthy 42-year-old man w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
13
1
1
Order By: Relevance
“…The DNNND repeats are in block II, and the DDNNNDNHNDD repeats are in block V. Profiles ms4760-1 to ms4760-35 have been described previously (5,18,25,53); ms4760-36 to ms4760-59 are described in this study. Profiles 4,10,11,13,14,16,17,19,20,22,25,26,28,29,30,31,32,33, and 34 were not observed in the present study. Other differences among sequences are indicated in boldface.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…The DNNND repeats are in block II, and the DDNNNDNHNDD repeats are in block V. Profiles ms4760-1 to ms4760-35 have been described previously (5,18,25,53); ms4760-36 to ms4760-59 are described in this study. Profiles 4,10,11,13,14,16,17,19,20,22,25,26,28,29,30,31,32,33, and 34 were not observed in the present study. Other differences among sequences are indicated in boldface.…”
Section: Resultscontrasting
confidence: 45%
“…First, the efficacy of quinine for the treatment of uncomplicated malaria is uncertain. A number of studies and case reports have demonstrated apparent failures after quinine therapy for falciparum malaria in Asia (9,41), South America (46,60), and Africa (22,31,38). Recent studies incorporating detailed assessments of treatment efficacy or effectiveness have shown 28-day failure rates of Ͼ10% after 7-day courses of quinine for uncomplicated malaria in Sudan (3), Thailand (40), and Uganda (1).…”
mentioning
confidence: 99%
“…The IC 50 s for isolates collected in Senegal were 31 to 765 nM in 1984 (Thies and Kaolack) [81], 5 to 932 nM in 1996 (Dielmo) [49] and 6 to 1291 nM in 2009 (Dakar) [40]. The wide range in QN susceptibility and recent evidence for QN treatment failure seen across Africa [82,83] or in Senegal in a patient who spent two months in Dielmo in 2007 [84] suggest that the evolution of parasites with reduced susceptibility may contribute to QN decreased efficacy. QN used in combination with DOX in the treatment of severe malaria in Dakar.…”
Section: Discussionmentioning
confidence: 99%
“…The first cases of QN clinical failure were observed in Brazil and Asia in the 1960s (4,12). In the 1980s, clinical failures became more frequent in Southeast Asia, South America, and Africa (13,15,19,22,33). However, QNR…”
mentioning
confidence: 99%